Inteligência artificial no Supremo Tribunal Federal e os reflexos sobre as matérias tributárias - Silva, Vinicius Ferrasso da (Universidade do Vale do Rio dos Sinos, 2020)
This research seeks to unite Legal Science and Computer Science, with the aim of determining the place of speech, which provides an adequate answer regarding this unprecedented experiment in the Supreme Court, without prejudice in the sense of deification of artificial intelligence and, nor of skepticism about AI systems. Thus, in order to achieve the general objective referenced, it has as specific objectives: in the second chapter, to visit the constitutional filters abroad, as well as to visit the history of the general repercussion from the relevance argument to the current scenario of the institute of general repercussion , highlighting the vague concept of the term general repercussion, which gives rise to the use (non)according to the discretion of the judge (cognitive bias), referenced in the leading case of Funrural's contribution, which declared it unconstitutional in (RE 596.177) and constitutionality in (RE 718,874); in the third chapter, the last specific objective is to study the tools that make up artificial intelligence, in order to build a pre-understanding of technology, in order to respond to the motor response: if the AI system in the processing of judgment Admissibility of Extraordinary Appeals would enable the necessary accountability to offer justice to the applicants; finally, in the fourth chapter, to identify the various AI systems already in operation in the Judiciary and, primarily, to study the characteristics of the Victor AI system built since 2017 by the Artificial Intelligence Laboratory of the University of Brasilia, in partnership with the Federal Supreme Court, in order to finally obtain the answer to the question of this thesis. That is, if the insertion of the IA Victor system in the processing of questions of general repercussion of tax matters submitted to the STF, observing the historical series of judgments of the theses of general repercussion of the constitutional question, as well as, the limits of applicability of the systems of AI in the judicial decision in this block of history, would the number of tax cases in the country decrease in the country? With these specific objectives in mind, it will be stated at the end that Artificial Intelligence, in processing the Extraordinary Appeal, tends to increase the processes of tax matters in the country. To do so, the research methodology used in this thesis will be the systemic-constructive methodological.
Keywords: Repercussão geral; Discricionariedade; Viese cognitivo; Viese algorítmico; Fundamentação jurídica; Inteligência artificial; General repercussion; Discretion; Cognitive bias; Algorithmic bias; Legal basis; Artificial intelligence; ACCNPQ::Ciências Sociais Aplicadas::Direito